Exemplar Selectivity Reflects Perceptual Similarities in the Human Fusiform Cortex. (25th February 2013) - Davidesco, Ido; Zion-Golumbic, Elana; Bickel, Stephan; Harel, Michal; Groppe, David M.; Keller, Corey J.; Schevon, Catherine A.; McKhann, Guy M.; Goodman, Robert R.; Goelman, Gadi; Schroeder, Charles E.; Mehta, Ashesh D.; et al.
Abstract : While brain imaging studies emphasized the category selectivity of face-related areas, the underlying mechanisms of our remarkable ability to discriminate between different faces are less understood. Here, we recorded intracranial local field potentials from face-related areas in patients presented with images of faces and objects. A highly significant exemplar tuning within the category of faces was observed in high-Gamma (80–150 Hz) responses. The robustness of this effect was supported by single-trial decoding of face exemplars using a minimal ( n = 5) training set. Importantly, exemplar tuning reflected the psychophysical distance between faces but not their low-level features. Our results reveal a neuronal substrate for the establishment of perceptual distance among faces in the human brain. They further imply that face neurons are anatomically grouped according to well-defined functional principles, such as perceptual similarity.